Palaeomagnetic data from Ediacaran (Vendian) sediments of the Arkhangelsk region, NW Russia: An alternative apparent polar wander path of Baltica for the Late Proterozoic-Early Palaeozoic - Iglesia Llanos, Maria Paula; Tait, J. A.; Popov, V.; Abalmassova, A. (Earth and Planetary Science Letters)
The study area is situated along the Zolotica river in NW Russia, located within the Kola-Dvyna Rift System in the Baltic Shield that developed during Meso and Neoproterozoic times. A 9-m thick section made up of shallow marine sediments of Upper Ediacaran age was sampled in this locality. Two volcaniclastic levels from the middle part of the section yielded an age of ∼556 Ma. (U/Pb SHRIMP-II on zircons). Two magnetic components were successfully isolated, component A (Decl = 157.1, Incl = 68.0, α95 = 1.9°, N = 575 in situ) carried by magnetite and component B (Decl = 120.3, Incl = - 31.7, α95 = 3.9°, N = 57, bedding corrected), carried by haematite. While component A is thought to represent a younger overprint direction, the in situ direction for component B on the other hand, is dissimilar to any expected younger direction and is considered to be primary magnetisation in origin, acquired during or soon after deposition of the sediments in the Late Ediacaran. The corresponding palaeomagnetic pole for component A in situ is located at Lon = 55.4°E, Lat = 31°N, A95 = 2.7° and for component B at Lon = 110°E, Lat = 28.3°S, A95 = 3.8°, N = 57. Combined with other palaeomagnetic poles of the same tectonostratigraphic unit an alternative apparent polar wander path for the Late Proterozoic-Early Palaeozoic of Baltica is proposed. Such an alternative path shows that after the mid Cryogenian (750 Ma), the poles that were situated over South Africa (p.d.c.) moved to the east until they reached Australia during the Late Ediacaran (555 Ma) where they remained approximately stationary until the beginning of the Cambrian (∼545 Ma). Finally, they moved to the northwest until they reached the Arabian Peninsula in the Early Ordovician. Palaeolatitudes indicate that Baltica situated near the equator from the Cryogenian through to the Ediacaran moving gradually to the south at c. 1 cm/yr. During the Late Early Ediacaran, the plate suddenly began to drift northward at c. 8 cm/yr and in the boundary with the Cambrian it was ...